Association between parents' trust in mental health professionals and disengagement from psychiatric service within the first 6 months of initial treatment of schizophrenia. Issue 4 (22nd June 2014) - Ishikura, Shigeko; Yamasaki, Syudo; Ando, Shuntaro; Nishida, Atsushi; Tanoue, Michika; Niimura, Junko; Asukai, Nozomu; Okazaki, Yuji
Abstract Aim To investigate the association between parents' encounter with reliable mental health professionals and disengagement from initial treatment among patients with schizophrenia. Methods This study was a part of the Reaching People Early Tokyo Survey. Participants were recruited from groups for family members of people with mental ill‐health around Tokyo. Self‐report questionnaires completed by 467 parents were analysed. Results Disengagement rate was 16.2% among patients whose parents met reliable mental health professionals within the initial 6 months, but 33.7% among patients whose parents did not report meeting such professionals. The odds of disengagement was less than half in the first group than in the second group (OR 0.38, 95% CI 0.21–0.67). Conclusions Establishing trust with family members might prevent disengagement from initial treatment among patients with schizophrenia. Mental health professionals should spend time to build a trusting relationship with families within the initial period of treatment.